The Effect of Brand Trust and Ease of Transaction on the Decision to Purchase Fashion Products at the Jiniso Jeans TikTok Shop - Astrid Puspita Dewi; Rahmah Hidayah; Dedy Dwi Arseto; Willy Cahyadi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the partial and simultaneous effects of the two independent variables on the dependent variable, namely purchasing decisions. The study employed a quantitative approach using a survey method. A sample of 100 consumers of Jiniso Jeans on TikTok Shop was selected through an accidental sampling technique. Primary data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 25 software, after passing validity, reliability, and classical assumption tests. The results of the study indicate that brand trust and transaction convenience have a positive and significant effect, both partially and simultaneously, on purchasing decisions. Simultaneously, these two variables explain 38.5% of the variation in purchasing decisions, while the remaining percentage is influenced by other factors. This study strengthens the relevance of the Technology Acceptance Model (TAM) in the context of social commerce and provides practical implications for local fashion businesses to strengthen brand trust while simplifying transaction processes in order to increase sales.